A Parametric Comparison Between the Behavior 1S0 and 3S1 of Helium and the Excited S-Stated of Neon in Helium Neon Laser - Abdulrahman, Parekhan M. (Sulaimani Journal for Pure and Applied Sciences, 2003)
Gas-discharges have a wide range of spectroscopic parameters including the after-glow excitations. If a fixed mixture of He and Ne is operated as a traditional discharge phenomenon,-then the important parameters could be measured spectroscopically. This project dims to parantetric comparison between the situation of both metastables of He states and the excited S-states of Ne in terms of different collision cross-sections, life-time considerations, spectral notations and many, other resonant transfer parameters. The results were expected to b favorable and suitable for our purposes and they were optimum for a mixture of He and Ne in low power gas lasers.
Keywords: MetaStable states; Spectroscopy of inert gases laser physics